Clinker-free CaO-activated silica fume as a cementitious binder for pavement application - Pranav, Shreyas (2024)
Ordinary Portland cement (OPC) production requires heating limestone up to 1450 °C and produces 0.5–0.9 kg of carbon dioxide for every 1 kg produced. Moreover, the massive volume of cement manufactured around the world every year adds to the urgent need to look for sustainable alternatives. This work proposes a novel calcium oxide (CaO)-activated high-volume silica fume mixture as a cementitious binder for pavement application that can address the sustainability concern with cement (because producing CaO requires a much lower calcination temperature than OPC, and that CaO is also used in low-volume in the binder). The combination of low-volume CaO and high-volume silica fume, particularly as a pavement binder has not been studied in the literature before. The compressive and flexural strength results showed that even by using a small fraction of CaO in the binder, it is possible to obtain acceptable strengths that satisfy ASTM pavement design guidelines, while OPC is unable to provide similar strengths at such low dosage. The mix having CaO content as 30 % of the silica fume content (CSF-30) shows the highest compressive strength (28d: 18.4 MPa) and flexural strength (28d: 4 MPa). In contrast, the maximum OPC-silica fume compressive and flexural strengths observed are 13.9 MPa and 2.9 MPa respectively at 28d From the microstructural results, it was seen that CaO–silica fume develops strength due to formation of calcite and calcium silicate hydrate. Almost all CaO–silica fume mixes exhibited lower porosity compared to their OPC-silica fume counterparts; CSF-30, the mix having the best mechanical performance showed the lowest porosity at 28d (2.8 %). A comparative sustainability analysis followed by a 5D analysis considering all the parameters studied in this work revealed that CSF-30 is the best binder alternative (overall score: 5.24). The results of this work will be useful for pavement users, designers, researchers, engineers, and relevant government officials, in having a sustainable clinker-free alternative pavement binder to OPC, particularly for low-volume roads, that satisfies the pavement design guidelines.